Is you okay? - Green, GloZell, 1972-; Parker, Nils (New York, NY : HarperOne, an imprint of HarperCollins Publishers, 2016)
"A fun, inspiring memoir from "the Queen of YouTube" about her journey from anonymity in Florida to massive popularity on the Internet, filled with the unlikeliest of stories that are as poignant as they are hilarious "Is you okay? Is you good? Cuz I want to know!" Eager to entertain, dedicated to making people laugh, comedian and video superstar GloZell Green is game for any challenge, no matter how silly, gross, or absurd. Her crazy video stunts have propelled her into the ranks of legendary funny ladies such as Ellen DeGeneres, Whoopi Goldberg, Tina Fey, Carol Burnett, Lucille Ball, and Phyllis Diller--and made her an inspiring icon for a new generation. With this funny and liberating book, GloZell uses the stories from her winding journey to unbelievable success to help her fans and young women everywhere navigate the obstacles we all face in life, while helping them find the greatness unique to each of them, inside and out. Is You Okay? speaks truth about the elements of life we wrestle with every day--empowerment, love, body image, school, work, family, relationships, failure, success. GloZell introduces some of her most outlandish, funny, and unforgettable video challenges and uses each to explore a serious yet common hurdle. Sharing formative stories and insights from her own life, she encourages young women to learn to love their body, break free of their shell, and carve out their own identity. Making the connection between hilarious physical challenges and meaningful personal challenges, GloZell shows that we're all in this together. "Everything isn't just gonna be okay. It doesn't just have to be good," she reminds us. "It can be great (even with a spoonful of pepper in your mouth).""--
Everyone's a little diff-uh-rent -- Age is just a number -- No excuses -- Always have faith -- Be yourself, be open to the path -- Haters gonna hate -- Find your Abby -- You're #1 -- Learn from your mistakes -- Stand out to break out.
Keywords: Green, GloZell, -- 1972-; YouTube (Electronic resource) -- Biography; Video blogs -- United States -- Biography; Internet users -- United States -- Biography; Women comedians -- United States -- Biography; Life skills